The Definition and Scope of Diagnostic Error in the US and How Diagnostic Error is Enabled. (15th January 2020) - Laposata, Michael
Abstract: Background: The quality of healthcare in the US has been progressively addressed by 3 reports from the National Academy of Medicine, the latest of which, entitled "Improving Diagnosis in Health Care, " was issued in 2015 from a 21-member panel (the author of this report was a member). The report is a review of the longstanding problem of diagnostic error. The infrastructure of healthcare delivery in the US has inadvertently made diagnostic error a major contributor to the high cost of care and preventable poor patient outcomes. Content: This review describes the failures in US healthcare delivery that have led to the overwhelming number of deaths attributable to diagnostic error. Each failure is associated with recommendations to eliminate it. The review begins with a description of the scope of the diagnostic error problem and then discusses each of the issues that need to be addressed to reduce the number of misdiagnoses. Summary: The problem of diagnostic error in the US is a large one. Some the contributing factors to this large problem can be resolved at a small expense and with modest change; others require a major overhaul of aspects of medical practice. For the first time, Americans have a "to-do list" to reduce our diagnostic error problem and be on par with other developed countries that are recognized as providing less costly care with better patient outcomes.